Bionomics and two sex life table of Coranus siva: A new potential predator of Fall armyworm (Spodoptera frugiperda) - S N, BHAGYASREE; TIMMANNA; H S, RAKSHITH; K B, RAMESH; B, GUNDAPPA; SUROSHE, SACHIN S (The Indian Journal of Agricultural Sciences, 2025)
A new generalist predatory bug, Coranus siva, was observed to feed on invasive fall armyworm [Spodoptera frugiperda (J E Smith)], which is currently creating a havoc in maize (Zea mays L.) cultivation. Though it’s naturally balancing the S. frugiperda population, its economic utilization is under bleak due to unavailability of scientific evidences on its bio-control potential. The present study was carried out during 2020–22 at ICAR-Indian Agricultural Research Institute, New Delhi to delineate its biology, life table and functional response to understand its bio-control potential. The bugs had total longevity of 52.7 ± 5.19 days with 90.14 ± 4.3% fecundity. The intrinsic rate of increase (r)/time unit was 9.59, the finite rate of increase (λ)/time unit was 1.10, the net reproductive rate (R0) was 63.10 and the mean generation time is 43.21, respectively. The C. siva exhibited Type II functional response against S. frugiperda. These findings gave the pragmatic clues and insights on utilization of C. siva as a promising bio-control agent for the management of S. frugiperda sustainably through integrated pest management.